Formalizing the Informal: A Critical Examination of Indonesia's Land Certification Program (PTSL) and Its Implications for Tenure Security and Social Equity - Henny Saida Flora; Seno Wibowo Gumbira2; Jimmy Nasroen; Dwi Nurahman; Suryani Intan Pratiwi Puwa (Inovasi Pratama Internasional. Ltd, 2026)
Indonesia’s Complete Systematic Land Registration Program (Pendaftaran Tanah Sistematis Lengkap, PTSL) has been heralded as a transformative initiative in the Global South’s land governance landscape. Launched in 2017 with the ambitious goal of registering all 126 million land parcels by 2025, the program has achieved a 94.4% registration rate. Despite this quantitative success, the program’s qualitative impacts on tenure security and social equity remain contested. This article critically examines PTSL through a qualitative, socio-legal lens, drawing on policy document analysis, semi-structured interviews with institutional actors, and case studies from three Indonesian provinces. The findings reveal a paradoxical outcome: while PTSL has significantly accelerated formal land registration, its procedural architecture ironically reproduces, rather than rectifies, pre-existing structural inequalities. Informal land tenure practices—customary ownership, inherited but undocumented rights, and gendered access—are systematically marginalized within the program’s bureaucratic framework. The certification process imposes financial burdens through BPHTB taxes that disproportionately exclude low-income households, while weak verification mechanisms have enabled land-grabbing by elite actors. Consequently, the program’s formalization agenda risks extinguishing long-standing customary tenure arrangements and reinforcing social stratification. The article argues that the technocratic focus on target attainment has fundamentally overshadowed substantive tenure security and distributive justice. It concludes by proposing a rights-based, community-centered model of land certification that recognizes legal pluralism, integrates gender-responsive mechanisms, and prioritizes protection of vulnerable groups